Differences of Imagery ability between youth soccer and swimming practitioners - Duarte-Mendes, P.; Marinho, D. A.; Serrano, J.; Paulo, R.; Faustino, A.; Ramalho, A.; Petrica, J. (Journal of Human Sport & Exercise, 2019)
Imagery (IM) is one of the most popular psychological techniques used by athletes and coaches to improve performance at competition level. Some authors refer that individuals with good movement IM ability learn better and improve their physical performances. Therefore, the purpose of this study was to verify the differences and the magnitude of effects on the imagery ability and three modalities (Visual Internal= VI; Visual External =VE; K=Kinesthesic) between youth soccer (team sport) and swimming (individual sport) practitioners. Sixty-two soccer practitioners and twenty-seven swimming practitioners from the Castelo Branco district volunteered to participate in this study. The Movement Imagery Questionnaire MIQ - 3 Portuguese version (Mendes et al., 2016) was used to assess imagery ability. Descriptive statistics (mean ± standard deviation) was performed for all variables under analysis. Data normality was tested using the Kolmogorov-Smirnov. Mann-Whitney and T-Test for Independent sample were used to verify the differences between groups. The magnitude of the effects was also calculated. The results suggest differences between groups (p<0,05) in all analysed variables (MIQ-3, VI, VE, K). The soccer practitioners reveal better scores in the total MIQ-3 Scores and in all subscales.